Eliciting Farmers’ Rice Trait Preferences in Southern Asia and South-eastern Asia through the Investment Game Application - Ynion, Jhoanne; Dixit, Shalabh; Paguirigan, Neale Marvin; Custodio, Marie Claire; Demont, Matty (CGIAR, 2024)
Breeding programs that respond to the future needs and preferences of stakeholders require forward-looking and participatory demand-elicitation approaches. We elicited farmers’ preferences for rice varietal trait improvements (VTIs) through the Investment Game Application (IGA). IGA enables farmers to design their ideal future varieties by strategically allocating a fixed breeding investment fund among 10–11 VTIs that could enhance their most preferred varieties, while accounting for breeding costs. A sample of 1,198 male and female farmers across Southern Asia and South-eastern Asia used IGA to design their future varieties for irrigated rice systems under varying levels of exposure to information on future market and climate change trends. Farmers mainly prioritized biotic stress tolerance over all other traits, followed by market-driven grain quality traits. They invested 33–65 percent of their funds in rice breeding for insect and disease resistance, mainly to address stem borer and blast. In line with market trends toward finer rice grains, they allocated 11–43 percent of their investment funds to grain quality traits such as slenderness. While farmers’ priorities largely corroborate the current seed product market segments and the traits prioritized in the corresponding target product profiles, they argue for a stronger emphasis on biotic stress resistance relative to abiotic stress tolerance, which was further confirmed through strong consensus between women’s and men’s trait priorities. Insights from IGA experiments can guide demand-driven and gender-intentional target product profile design in breeding pipelines to potentially accelerate varietal turnover in farmers’ fields.